Expatriates and managing global mobility
1 online resource.
Keywords: "This book sets out to examine the problem of expatriate management through an I/O Psychology lens. The authors draw upon the expertise of scholars from around the world to provide insights into the latest research findings and remaining needs, remaining to a wide variety of issues"--